The Subtle Residual - Elena Moskalenko (Università degli Studi di Torino, 2021)
The following essay analyzes significant Baroque substrata underlying in The Scarlet Letter, seized, inter alia, in relation to momentous Puritan legacy, an essential element of Nathaniel Hawthorne’s literary work. In particular, the paper focuses on analyzing crucial and minor Baroque topoi represented in the novel, such as metamorphosis, relativism and ambivalence of reality, anxiety and death obsession. Furthermore, the article investigates the role of sharp chromatism within The Scarlet Letter, use of typical Baroque symbols, such as ellipsis and maze, and the fundamental role of distinctive Baroque tropes, id est metaphor and antithesis.